Online Education Versus On-Site Education in the Pandemic Period - Teodorescu, Ana-Maria (An Overview of Literature, Language and Education Research Vol. 5, 2024)
Online education during the pandemic has led to changes in the education process. Teachers had to change their teaching methods. The students felt the effects of this change. The purpose of this study is to find out the opinion of students from a university in Romania regarding these changes. A total of 79 respondents participated in this study: 26 students of the Faculty of Letters and Science and 53 students of the Faculty of Economic Sciences at Petroleum and Gas University of Ploiesti, Romania. The aim of the study is to compare the students' opinions from the humanities specialization (Managerial and Administrative Assistance) and students from the economic specialization (Accounting and Business Informatics). The students answered questions focused on the educational and social sides. In order to answer some questions, students had to make an analysis of online learning versus traditional learning. The questions highlighted the need for students' IT knowledge for the optimal development of online education. From the answers, it is clear that it is necessary for students to have digital skills. The SWOT analysis shows the following aspects: Strengths: Participations (81% of respondents indicated that they attended courses more during this period); time (an advantage of online learning presented by 24 % of respondents and 16 % replied that they no longer have to commute, which involves financial benefits); motivation (44% of students responded that time allocated to the individual study was higher). Weaknesses: Social interaction (28% of students presented this as a disadvantage of online learning); lack of interest (12% replied that they could not concentrate on teachers' instructions if they were not in the classrooms). Opportunities: Technical advantages (62% replied that their Internet browsing knowledge was useful, and 52% replied that their PC operating knowledge was useful; getting a job during school placement is presented as an online learning advantage for 15 % of them). Threats: Technical difficulties (15% responded that a weak Internet connection represents one disadvantage).